2020
DOI: 10.1186/s13063-020-4117-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of LiuZiJue Qigong versus traditional core stability training for poststroke patients complicated with abnormal trunk postural control: study protocol for a single-center randomized controlled trial

Abstract: Background: Trunk function in stroke patients with hemiplegia is associated with respiration and core stability and is also found to be associated with balance and postural control and activities of daily living. LiuZiJue Qigong (LQG) is a traditional Chinese method of fitness based on breath pronunciation. The purpose of this study is to compare the clinical efficacy of LQG and traditional core stability training in the treatment of stroke patients with abnormal trunk posture. This protocol is written accordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…It is worth noting that LQG pays more attention to the training of exhalation ability, which is more suitable for stroke patients who present with a more pronounced decline in expiratory function ( 45 ). The LQG is employed to emphasize the adverse abdominal breathing method, which also contributes to respiratory functions ( 10 18 , 20 , 21 , 23 29 , 32 – 38 , 42 , 44 – 46 ). Therefore, LQG can improve the respiratory function of patients after stroke, and the respiratory function is beneficial to the improvement of balance ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that LQG pays more attention to the training of exhalation ability, which is more suitable for stroke patients who present with a more pronounced decline in expiratory function ( 45 ). The LQG is employed to emphasize the adverse abdominal breathing method, which also contributes to respiratory functions ( 10 18 , 20 , 21 , 23 29 , 32 – 38 , 42 , 44 – 46 ). Therefore, LQG can improve the respiratory function of patients after stroke, and the respiratory function is beneficial to the improvement of balance ability.…”
Section: Discussionmentioning
confidence: 99%
“…A MyLab color Doppler ultrasound diagnostic instrument with a probe frequency of 5-10 MHz was used to determine the thickness of the diaphragm and its mobility. Because the ultrasound image of the right diaphragm is clearer than the left, the right side was selected for uniform measurement by a specially trained physician ( 32 ). Diaphragm thickness was measured during quiet breath and deep breath ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The static balance abilities of sitting and standing were evaluated using the Prokin proprioception evaluation and training system (PK254P; TecnoBody, Italy). The operational details have been previously published ( Wang et al, 2020 ). The central of pressure (COP) trajectory (mm) and COP area (mm 2 ) in sitting and standing position were collected with eyes open and closed, with lower values indicating better balance.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that qigong exercises can improve the physical and mental state of patients who have had a stroke, could reduce the effects of sleep and mental disorders and improve muscle function [138][139][140][141].…”
Section: Strokementioning
confidence: 99%